ヒガシ ナンキョク ミズホ カンソク キョテン デ サイシュ サレタ 75m ボーリング コアー ノ コウゾウ カイセキ - 中尾, 正義; ナカオ, マサヨシ; NAKAWO, Masayoshi (国立極地研究所, 1974)
P(論文) 第12次日本南極地域観測隊(1971-1972年)によりみずほ観測拠点で75mのボーリングコアーが採取された.採取直後,密度が測定されるとともに水平薄片がつくられ,偏光写真撮影ののち,その結晶主軸方位が測定された.密度は深さとともに増加していくのに対して,平均結晶粒度は約35m深までほぼ一様であり,そこから急激に大きくなっていた.結晶粒度がほぼ一様な範囲においては,結晶主軸はほとんど鉛直方向を向いており. 35mより深くなるとその分布図は,鉛直軸まわりのガードル状を呈していた. A 75m-long snow/ice core was drilled at Mizuho Camp, East Antarctica, by the glaciological members of the 12th Japanese Antarctic Research Expedition (1971-1972), and its density and the orientations of the c-axes of crystal grains composing it were measured immediately after recovery. It was found that the density increased with the depth, but that the average grain size was almost constant down to about 35m, at which depth it began to show a sharp increase. At depths shallower than 35 m the directions of the c-axis were almost vertical, while the fabric patterns for the samples deeper than 35 m showed a so-called girdle pattern. departmental bulletin paper